Thursday

April 24, 2014

April 24, 2014

Posted by **Roy Jr** on Wednesday, December 14, 2011 at 10:27pm.

- math -
**MathMate**, Wednesday, December 14, 2011 at 11:39pmThere is no easy rule, because there are many terms.

The following identity could help:

(a+b+c)^3

=c^3+3bc^2+3ac^2+3b^2c+6abc+3a^2c+b^3+3ab^2+3a^2b+a^3

So substitute 2x for a, 3y for b and 4z for c. Do not forget that a^2 would mean (2x)^2=4x^2, a^3 would mean (2x)^3=8a^3 and so on.

A good way to check your work is to add up the coefficients, they should equal (2+3+4)^3 = 729.

- math -
**Reiny**, Wednesday, December 14, 2011 at 11:39pmvery patiently expand

(2x + 3y + 4z)(2x + 3y + 4z)(2x + 3y + 4z)

= ....

**Related Questions**

algebra - what is the solution of the system of equations. 2x+2y+3z=-6 3x+5y+4z=...

Stuck on this Algebra 2 question! - what is the solution of the system of ...

math - 2x+3y=6 (solve for x) 2x+3y=6 Get unknown on one side and everything else...

Math - Use the echelon method to solve the system: x + 3y + 4z = 14 2x – 3y +2z...

Calculus - Which plane goes through the origin and is perpendicular to the line ...

math - what is (x to the 3rd power + x to the 2nd power) divided by ((x+4)(X-4...

math - hi, i need help with solving this equation for "y" 2x+3y=-2 2x+3y=-2 Get ...

Math - evaluate the expression 2x-3y-4z x=7 y=-3 z=-1

Calc. - I am so confused with this last part of the unit! What in the world is ...

math 115 - - (-4)3rd power + (-3)2nd power - .5 3rd power is 72.875 correct? The...